2001
DOI: 10.1089/104303401300042429
|View full text |Cite
|
Sign up to set email alerts
|

AdTIMP-2 Inhibits Tumor Growth, Angiogenesis, and Metastasis, and Prolongs Survival in Mice

Abstract: TIMP-2 is a natural matrix metalloproteinase (MMP) inhibitor that prevents the degradation of extracellular matrix proteins. It abolishes the hydrolytic activity of all activated members of the metalloproteinase family and in particular that of MT1-MMP, MMP-2, and MMP-9, which are selective for type IV collagenolysis. Since MMPs have been implicated in both cancer progression and angiogenesis, we generated a recombinant adenovirus to deliver human TIMP-2 (AdTIMP-2) and evaluated its anticancer efficiency in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 51 publications
6
51
0
Order By: Relevance
“…The adenoviral doses reported in the literature on in vivo TIMP gene therapy are higher 25,26,28 than the dose we used, and resulted in higher hTIMP serum levels. 28 Adenoviruses have also been delivered directly into the tumor 24,27 or into normal, non-cancerous tissue to protect it against metastasis. 28 The main purpose of the study was to investigate whether constitutive expression of hTIMP gene products affected the outcome of TNF/IFNg antitumor therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adenoviral doses reported in the literature on in vivo TIMP gene therapy are higher 25,26,28 than the dose we used, and resulted in higher hTIMP serum levels. 28 Adenoviruses have also been delivered directly into the tumor 24,27 or into normal, non-cancerous tissue to protect it against metastasis. 28 The main purpose of the study was to investigate whether constitutive expression of hTIMP gene products affected the outcome of TNF/IFNg antitumor therapy.…”
Section: Discussionmentioning
confidence: 99%
“…13 TIMPs have a pronounced antitumor potential, first observed with recombinant TIMP [14][15][16] and later with tumor cells engineered to overexpress TIMPs. [17][18][19][20][21] Recent data have shown that in vivo gene therapy with TIMPs is an excellent treatment for established primary tumors, at least in small animal models, [22][23][24][25][26][27] and also protects normal, non-cancerous target tissue against metastases. 28,29 The primary aim of this research was to examine the effects of constitutive expression of TIMP gene products on the outcome of antitumor therapy with TNF/IFNg.…”
Section: Introductionmentioning
confidence: 99%
“…Retrovirus-mediated expression of TIMP-3 in tumor cells inhib- 145 MMP-2 Various IFN-a 147 EC proliferation/migration Angiostatin 148,149 Various Endostatin 117,150 MT1-MMP, MMP-2 Various Arresten 151 EC proliferation, migration Canstatin 152 EC viability, migration Tumstatin 153,154 EC viability, migration, protein synthesis Platelet factor 4 155 VEGF and bFGF signaling TIMP-1 156 Broad-range Various effects, including MMP inhibition TIMP-2 157 Broad-range Various effects, including MMP inhibition TIMP-3 138 Broad-range Various effects, including MMP inhibition TIMP-4 136 Broad-range Various effects, including MMP inhibition Exogenous/synthetic TNP-470 158 EC proliferation Squalamine 159 EC proliferation Captopril 160 MMP-2, MMP-9 EC migration Combretastatin-A4 161 EC tubulin CP-547, 632 162 VEGFR-2 and bFGF kinases Vitaxin 163 a v b 3 integrin, EC apoptosis EMD121974 164 a v b 3 and a v b 5 integrin COL-3 83 MMP-2, -9, -14 MMPs Neovastat 165,166 MMP-2, -9, -12 MMPs, designed to avoid sheddases BMS-275291 54 MMP-1, -2, -3, -7, -9, -14 Bevacizumab 167 VEGF ited tumor growth and angiogenesis in vivo. Tumors overexpressing TIMP-3 failed to form a functional vasculature and had reduced pericyte recruitment.…”
Section: Timps As Potential Antiangiogenic Agentsmentioning
confidence: 99%
“…Numerous experimental and clinical studies have indicated that the therapeutic efficacies of such treatment modalities essentially require continuous delivery of a large quantity of secretory therapeutic molecules. [13][14][15][16][17] Hence, gene delivery to endothelial cells should be able to allow boosting of the antiangiogenesis effect by their direct and durable transmission of the introduced therapeutic genes.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the capability of RCRs to integrate into host DNA makes them ideal candidates for long-term genetic modification of tumor cells which may be a considerable advantage for a number of genebased strategies, for example, anti-angiogenesis treatment or protease inhibitor-based therapy. [13][14][15][16][17] However, and despite these properties, the applicability of RCR vectors in cancer gene therapy has been limited, primarily due to the instability of replicating retroviruses carrying additional transgenes. [18][19][20] Previous studies have shown that replicating MLV carrying transgene sequences between 100 to 1200 bp within the U3 region of the 3 0 long terminal repeat (LTR) usually lost their inserts within a few passages.…”
mentioning
confidence: 99%